Synthesis, Characterization and Properties of a Novel Triphenylamine Substituted Oligo(phenylene vinylene) - Xu, Q.; Chen, H.-Z.; Huang, Y.-G.; Shi, M.-M.; Wang, M. (Asian Journal of Chemistry, 2010)
A novel hole transport material of triphenylamine-substituted oligo(phenylene vinylene) of 4,4'- bis-[2-[4-[N,N-bis-(4-bromophenyl-amino)]-phenyl-1-yl]-vinyl-1-yl]-1,1'-biphenyl was synthesized. Its molecular structure was characterized by FTIR and 1H NMR spectra as well as elemental analyses. Its spectroscopic and electrochemical properties were measured. The duallayer photoreceptors taking oxotitanium phthalocyanine as the charge generation material and the compound as the charge transport material were fabricated, whose photosensitivity was 1.11 cm2 μJ-1 at 762 nm, 1.6 times higher than that from N,N'-diethyl-4-aminobenzaldehyde-1-phenyl- 1'-(α-naphthyl)hydrazone as charge transport material. This indicates that the triphenylamine substituted oligo(phenylene vinylene) compound may be a promising candidate for application in optoelectronic devices.